Stress-induced secretion of α-melanocyte-stimulating hormone and its physiological role in modulating the secretion of prolactin and luteinizing hormone in the female rat - Khorram, Omid (1985)
The pattern of αMSH release during immobilization stress in ovariectomized rats was determined and correlated with that of plasma PRL and LH. Stress induced a marked elevation in plasma immunoreactive αMSH, with a time course identical to that of plasma PRL. The increment in plasma PRL was greater than that in plasma αMSH. Plasma LH was markedly lowered by stress. Analysis of pituitary and hypothalamic αMSH indicated a significant (P < 0.05) increase in the neurointermediate lobe and anterior lobe content of αMSH. The αMSH content in the hypothalamus was lowered by stress when expressed as tissue content (P < 0.025), although no significant differences in content in this area were detected when the results were expressed in terms of tissue protein. Stress induced a marked increase (P < 0.01) in the median eminence levels αMSH. In conclusion, αMSH of brain origin is released during stress and is involved in lowering plasma PRL to basal levels and producing a partial suppression of plasma LH. © 1985 by The Endocrine Society.